2(х - 7) = -2
2х - 14 = -2
2х = -2 + 14
2х = 12
х = 12 : 2
х = 6
Е) -5х+1,2=-5,1
-5х=-5,1-1,2
-5х=-6,3
х=6,3:5
х=1,26
Ответ: 1,26
б) 7,3х-1/3=-1,2х+3
7,3х+1,2х=3+1/3
8,5х=3 целых 1/3
8 целых 5/10х=3 целых 1/3
8 целых 1/2х=3 целых 1/3
х=3 целых 1/3:8 целых 1/2
х=10/3:17/2
х=10/3*2/17
х=20/51
Ответ: 20/51
1. 0,81=81/100 верно
2. 1,013=113/100 неверно
3. 16,29=1629/100 верно
4. 200,257=200257/1000 верно
3(2x-5)-(x-4)=6x
4(3х-1)-(7х+11)=9
(х-8)-(6х+14)=9х-1
3(7х+5)+(2-6х)=11-х
4х+8-(19-3х)=11
(х-3)-(х+8)+(6х-13)=8